Atmospheric emissions of one pulp and paper mill. Contribution to the air quality of Viana do Castelo - Silva, Lígia Torres (2009)
One of the most sensitive environmental impact of the pulp and paper mills is associated with the atmospheric pollution namely with sulphur compounds, particulate matter and nitrogen oxides. The study undertaken aimed to evaluate the influence of one pulp and paper mill to the air quality of a Portuguese city located in the vicinity. A range of numerical models were used to produce the concentration maps: the ADMS- Urban model for the pollutants dispersion; the Hills model to calculate air flow and turbulence over complex terrain, including the effects of variable surface roughness and EPER data (The European Pollutant Emission Register) to estimate the emissions factors.